Risk factors for perinatal mortality in Peruvian social security hospitals: EsSalud’s Perinatal Surveillance System data analysis - Arrieta-Herrera, Alejandro (2009)
This study uses information from the Perinatal Surveillance System (Sistema de Vigilancia Perinatal, SVP) of the Peruvian social security hospitals (EsSalud) to identify risk factors for perinatal mortality. The SVP includes health centers in all the country with different levels of hospital care. The study groups hospitals based on higher or lower levels of care in order to quantify the incidence of risk factors in each group. Finally, the study highlights the importance to keep an efficient clinical database that could be integrated with other health organizations in the country, in order to joint efforts to reduce perinatal mortality in Peru. Objectives: The first goal was to find the main risk factors for perinatal mortality in EsSalud’s hospitals. The second goal was to identify differences in the incidence of these factors on hospitals with higher and lower levels of care. Design: Descriptive, comparative and transversal study. Setting: EsSalud national hospitals net, Peru. Participants: Mothers and their newborns. Interventions: Clinical data from the SVP was used to estimate probability of death during the perinatal period; 108 813 newborns and their mothers whose deliveries were in years 2005 and 2006 were studied. Estimations were based on multivariate logistic models. Main outcome measures: Perinatal mortality. Results: Congenital anomaly was the most important risk factor for perinatal mortality in hospitals of lower and higher level of care (OR=30,99 and 15,26 respectively), followed by prematurity below 32 weeks (OR=15,68 and 4,20) and weight above 4 000 grams (OR=4,17 and 3,87). Maternal risk factors were also associated with perinatal mortality but with a lower incidence. The most important were genital bleeding after 24 weeks of pregnancy (OR=4,23 and 3,81), and other obstetric entities different from anemia, preeclampsia, and premature membrane rupture (OR=4,53 and 1,76). Conclusions: Risk factors identified in this study are consistent with medical literature on perinatal mortality. In hospitals with higher level of care the incidence of risk factors on mortality is lower, even though they concentrate the most risky patients and consequently the highest mortality. Hospitals with lower level of care require to focus resources on main risk factors, and to improve their referral systems. EsSalud’s SVP is a valid, consistent and useful tool to monitor and control perinatal mortality.